2015
DOI: 10.1177/0265659015601165
|View full text |Cite
|
Sign up to set email alerts
|

Specific language impairment (SLI) and reading development in early school years

Abstract: Specific language impairment (SLI) is a condition that affects children’s emerging language skills. Many different language skills can be affected in SLI, but not all individuals with SLI have the same set of difficulties. As a result, SLI is a highly heterogeneous condition. The ability to read and understand written text is a higher function of language, which has its base on the language skills that may be affected by SLI. Previous studies suggest that children with SLI are at risk of developing literacy di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 44 publications
3
17
1
5
Order By: Relevance
“…The main weakness of this study was the small number of the participants. Partially this was due to our relatively small cohort [30,31] and, thus, the number of case-control pairs remained small. This hampers possibilities to make clearcut conclusions about parameters which did not turn out to differ statistically significantly and allows only preliminary conclusions to be drawn from these parts of the data.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…The main weakness of this study was the small number of the participants. Partially this was due to our relatively small cohort [30,31] and, thus, the number of case-control pairs remained small. This hampers possibilities to make clearcut conclusions about parameters which did not turn out to differ statistically significantly and allows only preliminary conclusions to be drawn from these parts of the data.…”
Section: Strengths and Limitationsmentioning
confidence: 97%
“…The information of the pilot survey also conducted to the time scoring method used. Finally, the parents in this study filled in, during one week, daily questionnaires (see Appendix) where the observed time was between 5 pm and 9.30 pm each day and it was divided into [29][30][31]. The research included all children born in 1998 and 1999 who were diagnosed in specialist health care in Helsinki University Central Hospital as having SLI (ICD10 diagnosis F80.1 or F80.2) living in the city of Vantaa, Finland.…”
Section: Measurement Of Activities Atmentioning
confidence: 99%
“…The typical symptoms manifested by children with SLI initially resemble a delay in the development of speech; however, over time, the children exhibit a constellation of problems that can affect the following diverse aspects of language competencies: phonological, lexical, morphological, syntactic or pragmatic-semantic (Leonard, 2014). Notably, a diagnosis of SLI is a significant risk factor for the occurrence of reading and writing difficulties in school-aged children (Isoaho, Kauppila, Launonen, 2015, Williams, Larkin, Blaggan, 2013. Other impairments associated with this risk factor include problems with interpersonal relationships and irregularities in emotions and behaviour, particularly in patients with severe and difficult-to-treat forms of the disorder (Conti-Ramsden et al, 2013;Redmond & Rice, 1998).…”
Section: Specific Language Impairment (Sli)mentioning
confidence: 99%
“…La capacidad de leer y entender un texto escrito tiene su base en las habilidades del lenguaje oral, por lo que pueden verse afectadas por el Trastorno Especifico de Lenguaje (TEL), que constituye una "alteración significativa en la adquisición y desarrollo del lenguaje, que no está justificada por ninguna causa física, neurológica, intelectual ni sensorial, en unas condiciones sociales adecuadas" (Aguado, Coloma, Martínez, Mendoza, & Montes, 2015, p.147-148). Por ello, no es sorprendente que los niños con TEL manifiesten dificultades en la lectura (Bishop & Snowling, 2004;Catts, Bridges, Little & Tomblin, 2008;Isoaho, Kauppila, & Launonen, 2016).…”
Section: Introductionunclassified